Research of the Combined Trajectory Planning of Descartes Space and Joint Space - Lai Xiao; Liu Yong; Luo Wenguo; Dai Yanxia; Zeng Han (Jixie chuandong)
In order to get better meet the actual needs of trajectory,and to find a better method of trajectory planning,a combined space planning method for trajectory planning which combine Descartes space with joint space planning is found based on the former. Through the closed loop vector method,kinematics equation is established and the space trajectory is fitted based B spline function model,the motion curve of the joint space planning and the motion curve of Descartes space planning and the motion curve of combined space planning are obtained. Finally,through the prototype,the test verification is carried out. Through the analysis of the obtained results,it is found that the changes of the velocity and acceleration in the cycle time of combined space trajectory planning is better than the joint space trajectory planning or spatial planning of Descartes alone,and it will improve the quality of the whole movement of high level stability and reduce the impact in the movement process. Comparing with the experimental results,the movement trend tend to be consistent,the part of the curve have subtle difference and need further optimization but the method has very important significance for machine operation.